A comprehensive immunohistochemical analysis of IMP2 and IMP3 in 542 cases of ovarian tumors - Kristýna Němejcová; Michaela Kendall Bártů; Romana Michálková; Jana Drozenová; Pavel Fabian; Oluwole Fadare; Jitka Hausnerová; Jan Laco; Radoslav Matěj; Gábor Méhes; Naveena Singh; Simona Stolnicu; et al. (BMC, 2023)
Abstract Background IMP2 and IMP3 are mRNA binding proteins involved in carcinogenesis. We examined a large cohort of ovarian tumors with the aim to assess the value of IMP2 and IMP3 for differential diagnosis, and to assess their prognostic significance. Methods Immunohistochemical analyses with antibodies against IMP2 and IMP3 were performed on 554 primary ovarian tumors including 114 high grade serous carcinomas, 100 low grade serous carcinomas, 124 clear cell carcinomas, 54 endometrioid carcinomas, 34 mucinous carcinomas, 75 mucinous borderline tumors, and 41 serous borderline tumors (micropapillary variant). The associations of overall positivity with clinicopathological characteristics were evaluated using the chi-squared test or Fisher's Exact test. Results We found IMP2 expression (in more than 5% of tumor cells) in nearly all cases of all tumor types, so the prognostic meaning could not be analyzed. The positive IMP3 expression (in more than 5% of tumor cells) was most common in mucinous carcinomas (82%) and mucinous borderline tumors (81%), followed by high grade serous (67%) and clear cell carcinomas (67%). The expression was less frequent in endometrioid carcinomas (39%), low grade serous carcinomas (23%), and micropapillary variant of serous borderline tumors (20%). Prognostic significance of IMP3 could be evaluated only in low grade serous carcinomas in the case of relapse-free survival, where negative cases showed better RFS (p = 0.033). Conclusion Concerning differential diagnosis our results imply that despite the differences in expression in the different ovarian tumor types, the practical value for diagnostic purposes is limited. Contrary to other solid tumors, we did not find prognostic significance of IMP3 in ovarian cancer, with the exception of RFS in low grade serous carcinomas. However, the high expression of IMP2 and IMP3 could be of predictive value in ovarian carcinomas since IMP proteins are potential therapeutical targets.